2014
DOI: 10.1128/aac.01946-13
|View full text |Cite
|
Sign up to set email alerts
|

In VivoEfficacy of Human Simulated Regimens of Carbapenems and Comparator Agents against NDM-1-Producing Enterobacteriaceae

Abstract: e Doripenem and ertapenem have demonstrated efficacy against several NDM-1-producing isolates in vivo, despite having high MICs. In this study, we sought to further characterize the efficacy profiles of humanized regimens of standard (500 mg given every 8 h) and high-dose, prolonged infusion of doripenem (2 g given every 8 h, 4-h infusion) and 1 g of ertapenem given intravenously every 24 h and the comparator regimens of ceftazidime at 2 g given every 8 h (2-h infusion), levofloxacin at 500 mg every 24 h, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
31
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 39 publications
4
31
1
Order By: Relevance
“…A moderate reduction in bacterial density was demonstrated for ceftazidime alone against the isogenic NDM strain despite an fT ϾMIC (percentage of the dosing interval during which free drug concentrations exceed the MIC) of 0%. Similar to our previous studies, these data suggest that the in vivo effectiveness of this enzyme in reducing the antibacterial activity of the compound is discordant with the observations derived from in vitro MIC testing (8,9). However, against the four clinical NDM-producing strains, all of which were tested with in vitro ceftazidime MIC values of Ͼ128 g/ml, ceftazidime failed to show activity, likely due to the coproduction of other ␤-lactamases (e.g., ESBLs, OXAs), which is consistent with previously published in vivo observations of other NDM-producing clinical isolates (4,9).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…A moderate reduction in bacterial density was demonstrated for ceftazidime alone against the isogenic NDM strain despite an fT ϾMIC (percentage of the dosing interval during which free drug concentrations exceed the MIC) of 0%. Similar to our previous studies, these data suggest that the in vivo effectiveness of this enzyme in reducing the antibacterial activity of the compound is discordant with the observations derived from in vitro MIC testing (8,9). However, against the four clinical NDM-producing strains, all of which were tested with in vitro ceftazidime MIC values of Ͼ128 g/ml, ceftazidime failed to show activity, likely due to the coproduction of other ␤-lactamases (e.g., ESBLs, OXAs), which is consistent with previously published in vivo observations of other NDM-producing clinical isolates (4,9).…”
supporting
confidence: 87%
“…While the novel non-␤-lactam ␤-lactamase inhibitor avibactam has been shown to restore the in vitro potency of ceftazidime against Ambler class A and C (and some class D) ␤-lactamases, the combination of ceftazidime and avibactam displays high MICs in vitro against Enterobacteriaceae isolates that produce metallo-␤-lactamases, such as NDM (5-7). Of note, previous work conducted by our group with carbapenems raised a question about the potencies of these NDM enzymes in vivo (8,9). Contrary to the observed in vitro resistance, human simulated doripenem and ertapenem regimens demonstrated in vivo efficacies against isogenic and clinical NDM-1-producing isolates in a murine thigh infection model.…”
mentioning
confidence: 87%
“…Treatment regimens using carbapenems may be an option when the MICs of carbapenems are Յ8 mg/liter when a second antibiotic is added or when a prolonged intravenous infusion regimen is used (123,124). Encouraging results have been obtained with VIM and OXA-48 producers in humans and with NDM producers in animal models (106,125,126). Studies performed with an animal model of infection (i.e., mouse pneumonia) suggested that dual-carbapenem therapy (i.e., meropenem plus ertapenem) may be effective (126).…”
Section: Treatment Of Infections Due To K Pneumoniae With Carbapenemmentioning
confidence: 99%
“…Encouraging results have been obtained with VIM and OXA-48 producers in humans and with NDM producers in animal models (106,125,126). Studies performed with an animal model of infection (i.e., mouse pneumonia) suggested that dual-carbapenem therapy (i.e., meropenem plus ertapenem) may be effective (126). Ertapenem most likely acts as a "suicide" molecule for carbapenemase activity, whereas the more active drug, meropenem, retains its efficacy.…”
Section: Treatment Of Infections Due To K Pneumoniae With Carbapenemmentioning
confidence: 99%
“…Most interestingly, animal studies (mouse thigh infection) showed that both doripenem and ertapenem were effective against the metallo-b-lactamase (MBL) NDM-producing but not against KPC-producing K. pneumoniae isolates exhibiting similar levels of resistance to the latter drug (Wiskirchen et al, 2013(Wiskirchen et al, , 2014. Moreover, using the same animal model, increased doses of imipenem exhibited measurable bactericidal activity against K. pneumoniae resistant to the latter drug owing to production of another clinically important MBL, VIM-1 (Daikos et al, 2007).…”
mentioning
confidence: 99%